PHARMACOGNOSTICAL STANDARDIZATION OF HUGONIA MYSTAX L. LEAVES - G. Penchala Pratap; Sudarsanam, G.; Jyothi, B.; Prasad, G.P. (International Journal of Ayurveda and Pharma Research, 2015)
The present study discloses detailed pharmacognostical profile of leaves of Hugonia mystax L. This plant belongs to family Linaceae and an important medicinal plant in the Indian system of medicine. This species is has a restricted global distribution, occurring only in India and Sri Lanka. In the present study leaves of H. mystax were subjected for macroscopical, microscopical, physicochemical, phytochemical, fluorescence and H.P.T.L.C. analysis. The microscopical studies revealed the presence of shield shaped vascular bundle accompanied by 2 to 1 small accessory vascular bundles in the midrib region, pericyclic fibers around the vascular bundle, rubiaceous type stomata in lower region, presence of abundant rhomboidal to prism shaped calcium oxalate crystals, presence of reddish tannin content in palisade region and presence of abundant fibers. To determine extent of adulteration as well as to establish the quality and purity of drug, Physicochemical parameters like loss on drying, total ash value, acid insoluble ash, water insoluble ash, various extractive values etc., were carried out and revealed the total ash value as 8.7%, of which, 1.34% was acid insoluble ash, and 2.25% was water soluble ash and 5.8 % water insoluble. The extractive values were found to be 18.54% and 13.42% for water and alcohol respectively, which indicated higher extractive value for water compared to alcohol. Further, qualitative tests for various functional groups like Triterpenoids, alkaloids, glycosides etc., were carried out and H.P.T.L.C. profile was also established with Methanolic extract.